If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -5 = -20 Reorder the terms: -5 + 5y = -20 Solving -5 + 5y = -20 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 5y = -20 + 5 Combine like terms: -5 + 5 = 0 0 + 5y = -20 + 5 5y = -20 + 5 Combine like terms: -20 + 5 = -15 5y = -15 Divide each side by '5'. y = -3 Simplifying y = -3
| 10v-9v=12 | | 3x^2+315=18x | | 2j-9=9 | | 9/14-4/12 | | 20t-14t=6 | | 26+4x=90 | | 6x^3-12x^2+4x=0 | | x^2+y^2-2x-18y+46=0 | | 3=p/4-2 | | 8(7-p)=16(p-2) | | 6+2(x+8)3x+11+x= | | 2x+3=7(x-4) | | 1.5x-25+x=221 | | 32=8+6z | | 24-2f=20 | | 5x+7x=3x+6x | | 4+4k=20 | | 3=12-3y | | p/10-1=1 | | f(x)=3sinx+7 | | 9j-14=49 | | b=5ac-7aforc | | 7d+6=76 | | 16=4f+8 | | 3x*x*2x=480 | | lg(sqrtx+5)+lg(sqrtx-2)=12lg | | b/3-1=3 | | 2cos^2x+11sinx-7=0 | | 20+7n=97 | | 8(s+2)=96 | | 2n+3+n=n+11 | | 7h^2+7=-109 |